Efficacy and safety of new direct oral anticoagulants in chronic kidney disease: AHA 2019 updated guidelines and review of the literature - Stępak, Hubert; Krasiński, Zbigniew; Jawień, Andrzej; Ahmadi, Navid; Lipowski, Adam; Stanisic, Michał (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2019)
Direct oral anticoagulants (DOACs) are the drug of choice for the treatment of atrial fibrillation-associated systemic embolism and reducing the risk of strokes in chronic kidney disease (CKD) patients. DOACs have fewer drug-to-drug interactions as well as fewer side effects, compared to warfarin. This article compiled up-to-date research on the use of DOACs in CKD patients, taking the AHA 2019 guidelines into consideration. The aim of this article was to compare the efficacy and safety of DOACs with warfarin and to assess whether DOACs are a better alternative to warfarin. Among DOACs, apixaban has been shown to have the best outcome compared to other DOACs. As a result, the AHA 2019 updated guidelines have recommended warfarin and apixaban to be the first line agents for CKD patients. This review concluded that DOACs are better option in patients with mild to moderate CKD and excluding apixaban other DOACs are not indicated in patients with CrCl < 25 ml/min.